Projections overview and highlights, 2016-26. - Lacey, T. Alan; Toossi, Mitra; Dubina, Kevin S.; Gensler, Andrea B. (Monthly Labor Review, 2017)
Changing demographics in the population will have far-reaching effects on the labor force, the economy, and employment over the 2016-26 decade. The overall labor force participation rate is projected to decline as older workers leave the labor force, constraining economic growth. The aging baby-boomer segment of the population will drive demand for healthcare services and related occupations.